Halal pet essentials: pioneering halal certified pet products in Malaysia / Mohd Shafiz Saharan ... [et al.] - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar; Nazihah, Nurdiyana; Hassam, Siti Fairuza (Universiti Teknologi MARA, Kedah, 2024)
Halal Pet Essentials seeks to establish a niche market in Malaysia by offering halal-certified pet food and supplies to cater the needs of Muslim pet owner. This article explores the strategic planning, market analysis, and operational framework that is crucial in the development and sustainability of the business. The business is emphasizing high-quality and ethically produced products that comply with Syariah. In addition, the business aims to address a significant market gap while leveraging the Resource-Based View (RBV) theory to attain sustainable competitive advantage. The Resource-Based View (RBV) theory helps Halal Pet Essentials grow by leveraging unique, valuable, rare, inimitable, and non-substitutable resources such as halal certification, highquality ingredients, niche market focus, and a strong brand reputation for ethical practices. These resources differentiate the company from competitors and provide a sustainable competitive advantage. Growth strategies include building brand awareness, educating customers, developing innovative products, offering personalized services, and expanding geographically. Besides, strategic partnerships, diversification into complementary services, and technology integration further enhance customer experience and market reach will ensure that Halal Pet Essentials can effectively address market gaps and achieve sustainable growth in the halal pet product industry.